Management of Hydronephrosis Secondary to Isolated Renal Tuberculosis: A Case Report - Zamari Noori; Mohammad Jawid Nazari (Medical Science: Trends and Innovations Vol. 6, 2025)
Tuberculosis is a chronic granulomatous disease which may affect pulmonary and extrapulmonary organs. Isolated renal tuberculosis is a rare form of extrapulmonary TB, especially in immunocompetent individuals. This case report details the diagnosis and management of a 14-year-old male who presented with massive hydronephrosis of unknown cause. Initial investigations, including urine cultures, were inconclusive. However, percutaneous nephrostomy provided a key diagnostic opportunity. This case highlights the importance of considering TB in the differential diagnosis of patients with unexplained urinary tract abnormalities, even in immunocompetent patients. This case underscores the importance of considering TB in the differential diagnosis of patients with unexplained urinary tract symptoms, even in immunocompetent individuals.